Division of Labor and Maternal Gatekeeping during the Second Wave of COVID-19 in Turkey. - Aytac, F. Kubra; Schoppe-Sullivan, Sarah J. (Journal of Child & Family Studies, 2024)
The current study examined mothers' and fathers' division of paid and unpaid labor, and their perceptions of maternal gatekeeping (i.e., maternal behaviors and attitudes that inhibit or encourage father involvement in parenting), based on their work context (at home engaged in remote paid work or engaged in unpaid work, or working for pay outside the home) during the second wave of COVID-19 in Turkey (July–October 2020). Ninety-one Turkish couples (N = 182) with at least one child between 0 and 5-years-old participated in this study. In twenty-nine couples (n = 58), both parents were at home and engaged in either paid or unpaid work, while in eighteen (n = 36) only fathers were at home and mothers were working for pay outside the home, and in forty-four (n = 88) only mothers were at home and fathers were working for pay outside the home. Participants completed an online survey including questions on demographic information, the division of paid and unpaid labor, and maternal gatekeeping. Regardless of the couple's work context, time spent in housework and childcare activities reported by mothers was significantly higher than that of fathers. Fathers perceived higher maternal gatekeeping than mothers, and this was consistent across work context. Results demonstrate the persistence of gendered patterns of the division of labor and maternal gatekeeping in Turkish households regardless of work contexts during COVID-19. Highlights: Turkish women spent more time on housework and childcare activities than fathers during COVID-19. Turkish fathers perceived higher maternal gatekeeping than mothers, regardless of work context during COVID-19. Gendered patterns of the division of labor in Turkey persist despite changing work contexts during COVID-19.